Community solar: residents’ willingness-to-pay and the role of values, beliefs and energy situation - Wesseler, David Douglass (My University, 2025)
As solar photovoltaic energy demand expands and develops, community solar has arisen as an option for providing solar energy to households with limited access, for rural communities, and for other segments of the population who may have limited access to solar energy. Community solar applies to solar power generated by local utilities or firms that is shared among multiple households, who subscribe as members of the community system. Unlike traditional rooftop systems, community solar allows individuals to benefit from shared solar installations, making it available to renters, lower-income households, and those unable to install panels themselves. Understanding what influences residents’ willingness to pay to participate in these programs is needed for program and market development across different communities in order to develop rate structures and inform market, utilities and communities about the potential for such opportunities. The purpose of this thesis is to examine residents’ willingness to pay for a hypothetical community solar program. Furthermore, we wish to understand how values, beliefs, energy situation and household characteristics influence potential participation in such programs. We collected primary survey data from online panels in 2024 that resulted in 2910 usable observations across Kansas, Texas, Colorado, Oklahoma, Nebraska, and Iowa. Using a multiple bounded dichotomous choice (MBDC) valuation approach, we estimated the willingness to pay for community solar and how personal values and environmental beliefs; household demographics, household characteristics, and indicators of respondents’ energy situation influence willingness to pay (WTP) and participate in a community solar program. In addition, we assessed how WTP differed across population segments based on their perceptions about solar energy. We find that a number of factors including altruism toward humans and nature, self-interest, traditionalism, and openness to change values; environmental worldviews; energy security; demographics such as educational attainment, racial identity, household size; household characteristics such as electric heating; and state of residence can significantly influence WTP of individuals for community solar. In addition, perceptions about solar power influence the level of WTP across different population segments. This information can help to provide good insight for designing incentives and rate structures, help to develop marketing and educational strategies, and guide policy decisions that relate to community solar investments and projects.
Keywords: Community solar; Willingness to pay; Value-Belief-Norm theory